PEMANFAATAN TEKNIK TWEENING PADA ANIMASI 2D UNTUK EDUKASI GIZI IBU HAMIL DAN PENCEGAHAN STUNTING - Awwali Zahra Brillianti; Dani Arifudin; Deuis Nur Astrida (LPPM Universitas Abdurrab, 2026)
Stunting remains a significant public health issue that affects children’s growth and development, highlighting the need for effective educational media for pregnant women to improve their understanding of nutrition. This study aims to develop a 2D educational animation themed B2SA by applying tweening techniques as the primary method to achieve consistent motion and a more efficient production process. The research method includes pre-production (idea development, concept creation, storyboard, and asset design), production (asset creation, layout, and animation), and post-production stages (editing, rendering, and alpha testing), complemented by validation from health experts and animation specialists. The results indicate that the animation is deemed feasible based on expert assessment, with tweening increasing production efficiency by 90–97% in reducing manual frames compared to frame-by-frame animation while producing smooth, stable motion aligned with educational needs. The study concludes that the developed animation is feasible as an educational medium for pregnant women in supporting stunting prevention efforts.